2011
DOI: 10.1111/j.1365-3083.2010.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Acute and Chronic Allograft Rejection by Combinations of Tolerogenic Dendritic Cells

Abstract: It is well known that adoptive transfer of donor‐derived tolerogenic dendritic cells (DC) helps to reduce acute allograft rejection. However, this method cannot effectively prevent grafts from infiltration of inflammatory cells and fibrosis, and thus has minimal effect on chronic allograft rejection. In this study, we used mitomycin C (MMC) to generate tolerogenic DC and demonstrated that donor (Balb/c)‐derived MMC‐DC could induce hyporesponsiveness of recipient (C57BL/6) T cells in vitro, potentially by induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Donor-derived DCs were thought to reduce acute allograft rejection, but could not prevent the infiltration of inflammatory cells and fibrosis in the graft [9]. Donor and F1-derived DCs acted synergistically to induce immune tolerance and inhibit both acute and chronic transplant rejection in mice [9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Donor-derived DCs were thought to reduce acute allograft rejection, but could not prevent the infiltration of inflammatory cells and fibrosis in the graft [9]. Donor and F1-derived DCs acted synergistically to induce immune tolerance and inhibit both acute and chronic transplant rejection in mice [9].…”
Section: Discussionmentioning
confidence: 98%
“…The generation of regulatory T cells by injecting tolerogenic dendritic cells (DCs) has been investigated by several groups [3,9,10] and tolerogenic DC therapy was recently used in transplantation [11]. DCs are bone-marrow-derived antigen-presenting cells that have a recognized tolerogenic capability [12] and maintain both central and peripheral tolerance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Allograft rejection is induced by DCs presenting donor antigens from the graft to recipient's T lymphocytes. DCs from host taking up, processing and presenting donor's MHC molecules to host's T cells is thought to play a capital role in chronic rejection, and has been recognized as a major threat to longterm graft survival and stable allograft function (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis of cardiac myocytes, myocardial inflammation and contractile dysfunction are considered to be the hallmarks of cardiac allograft rejection [5][6][7][8][9]. Recent reports have shown that both innate and adaptive immunity contribute to acute organ transplant rejection, which affects allograft survival a lot [2,10].…”
Section: Introductionmentioning
confidence: 99%